Altered Monocyte and Langerhans Cell Innate Immunity in Patients With Recurrent Respiratory Papillomatosis (RRP) - Israr, Mohd; DeVoti, James A.; Lam, Fung; Abramson, Allan L.; Steinberg, Bettie M.; Bonagura, Vincent R. (Frontiers in Immunology, 2020)
The micromilieu within respiratory papillomas supports persistent HPV infection and disease recurrence in patients with recurrent respiratory papillomatosis (RRP). These patients show polarized (TH2-/Treg) adaptive immunity in papillomas and blood, enriched immature Langerhans cell (iLC) numbers, and overexpression of COX-2/PGE2 in the upper airway. Blood monocyte-derived iLCs and tissue-derived iLCs from RRP patients and controls were now studied to more fully understand innate immune dysregulation. Patients’ monocytes generated fewer iLCs than controls, due to a reduced fraction of classical monocytes that generated most, but not all the iLCs. PGE2, which was elevated in RRP plasma, reduced monocyte-iLC differentiation from controls to the levels from patients, but had no effect on subsequent iLC maturation. Cytokine/chemokine responses by iLCs from papillomas, foreskin and abdominal skin differed significantly. Freshly derived tissue iLCs expressed low CCL-1, and high CCL-20 mRNAs and were unresponsive to IL-36γ stimulation. Papilloma iLCS uniquely expressed IL-36γ at baseline, and expressed CCL1 when cultured overnight outside of their immunosuppressive microenvironment without additional stimulation. We conclude that monocyte/iLC innate immunity is impaired in RRP, in part due to increased PGE2 exposure in vivo. The immunosuppressive papilloma microenvironment likely alters iLC responses, and vice versa supporting TH2-like/Treg HPV-specific adaptive immunity in RRP.